Relationship between Resilience and the Quality of Life in university students of Cajamarca - Chávez-Hinostroza, Esthefani Fiorella (2020)
This study aimed to determine the relationship between resilience and the quality of life of students of a public university in Cajamarca. A group of 369 students of both sexes, of different cycles and belonging to all the faculties of the institution were evaluated. The measuring instruments were the Resilience Scale of Wagnild & Young and the Quality of Life Scale of Olson & Barnes. The results show a significant direct relationship between resilience and quality of life, as well as resilience and the dimensions of quality of life: Home and economic well-being; Friends, neighborhood and community; Family life and extended family; Education and leisure; Media; Religion and Health. It is concluded that resilience is a determining factor for the achievement of well-being which results in the quality of life of students contributing to their development in each domain of the life cycle.